Hubungan Pola Asuh Orangtua terhadap Kejadian Obesitas pada Anak Usia Sekolah - Komang Yogi Triana; Ni Made Pande Lilik Lestari; Ni Made Ririn Anjani; Ni Putu Pristha Dewi Yudiutami (Poltekkes Kemenkes Bengkulu, 2020)
Obesity had known as a condition of excessive levels of fat in a person's body which is can result in the emergence of chronic diseases. Currently the problem of obesity has been experienced by many children. One of the main actions to deal with obesity on childhood is through the closest person, they were the family. This study aimed to determine the relationship of parenting style applied by parents to the incidence of children obesity that occurs in the elementary school of Badung Regency, Bali Province. The research method in this research was crossectional study with a total sampling technique. This research was conducted at two elementary school in Badung Regency involving 96 students from grades 5 and 6. The analysis of this study used the Chi Square test which shows the results of p value = 0.03 <α. It means that there was a significant relationship between parenting style to the incidence of obesity in school-age children in the Badung regency. Thus, parents are expected to be able to apply good parenting style by not being too permissive or forcing children in order to build the character of children and support proper nutritional status according to the child's age.